CD4+CD25+ T(R) cells suppress innate immune pathology through cytokine-dependent mechanisms. - Maloy, K; Salaun, L; Cahill, R; Dougan, G; Saunders, N; Powrie, F (2003)
CD4(+)CD25(+) regulatory T (T(R)) cells can inhibit a variety of autoimmune and inflammatory diseases, but the precise mechanisms by which they suppress immune responses in vivo remain unresolved. Here, we have used Helicobacter hepaticus infection of T cell-reconstituted recombination-activating gene (RAG)(-/-) mice as a model to study the ability of CD4(+)CD25(+) T(R) cells to inhibit bacterially triggered intestinal inflammation. H. hepaticus infection elicited both T cell-mediated and T cell-independent intestinal inflammation, both of which were inhibited by adoptively transferred CD4(+)CD25(+) T(R) cells. T cell-independent pathology was accompanied by activation of the innate immune system that was also inhibited by CD4(+)CD25(+) T(R) cells. Suppression of innate immune pathology was dependent on T cell-derived interleukin 10 and also on the production of transforming growth factor beta. Thus, CD4(+)CD25(+) T(R) cells do not only suppress adaptive T cell responses, but are also able to control pathology mediated by innate immune mechanisms.